Risk Factors for Intrauterine Device Malposition - Ann C. Frisse; Jay B. Louik; Isha A. Kachwala; Haotian Wu; Nicole Felix; Thammatat Vorawandthanachai; Karina Avila; Nerys C. Benfield (Journal of Scientific Innovation in Medicine)
Objective: To identify risk factors for Intrauterine Device (IUD) malposition on ultrasound and develop a model to predict who may be at risk for IUD malposition. Methods: We performed a retrospective cohort study of IUD users with ultrasounds performed between July 2014 and July 2017 within a large urban medical system. Our primary outcome was IUD malposition. We used Fisher’s Exact Test and Wilcoxon Rank Sum Test to compare clinical characteristics between patients with malpositioned and non-malpositioned IUDs. We then selected variables and applied them to the least absolute shrinkage and selection operator (LASSO), elastic net, and logistic regression models. Results: Of 1,759 ultrasounds demonstrating the presence of an IUD, 436 described IUD malposition of which 150 were described as embedded and 16 were described as perforated. There were no significant differences in clinical characteristics between participants with malpositioned and non-malpositioned IUDs except a 1.2-year difference in mean age. Radiologists, compared to gynecologists, were more likely to describe an IUD as malpositioned (RR = 1.53, 95% CI: 1.21, 1.99). Abnormal uterine bleeding (AUB) as an indication for the ultrasound and fibroids visualized on ultrasound were more common in the malposition group compared to the non-malpositioned group (19.7% compared to 14.9%, p = 0.02 and 21.6% compared to 15.9%, p < 0.01 respectively). No linear combinations of any subset of variables predict the likelihood of having IUD malposition. Conclusion: Participants with IUDs described as malpositioned on ultrasound report were more likely to have their ultrasound interpreted by a radiologist, be 1.2 years younger, have an ultrasound performed for the indication of AUB, and have fibroids mentioned in their report.